Dampak Fatherless terhadap Perkembangan Individu - Nada Izdihar Firdausa; Adinda Fortuna; Icha Diana Putri; Jingga Tsabitah; Nada Aisya Hasanah Bustami; Roza Eva Susanti (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The role of fathers in the development of children is very important, but there are still many children who grow up without fathers and this is called fatherless. This study aims to describe the causes and developmental impacts of the fatherless phenomenon. This research used the literature study method and obtained 25 journals from various sources. This study found that the fatherless phenomenon has an impact on individual development such as cognitive development, language and communication development, socio-emotional development, and moral development. Based on the analysis obtained, socio-emotional development is the most common finding and has impacts such as difficulty building trust in others, difficulty expressing feelings and experiencing identity confusion. The causes of fatherlessness are divorce and patriarchy.